Risk Management Systems for Contingent Infrastructure Liabilities : Applications to Improve Contract Design and Monitoring - Lewis, Christopher M.; Mody, Ashoka (World Bank, Washington, DC, 2012)
Government guarantees for private infrastructure projects represent real liabilities, and their costs can average as much as a third of the amount guaranteed. The authors show how governments can use a risk valuation process to analyze the distribution of risks, decide which risks they should bear and which should be borne by the private sector, and reduce the frequency and size of calls on guarantees.